This is Your Brain on Music: Understanding a Human Obsession - Levitin, Daniel (London Atlantic Books, 2007)
This is the first book to offer a comprehensive explanation of how humans experience music and to unravel the mystery of our perennial love affair with it. Using musical examples from Bach to The Beatles, he reveals the role of music in human evolution, shows how our musical preferences begin to form even before we are born and explains why music can offer such an emotional experience. Levitin demonstrates how composers exploit the way our brains make sense of the world in order to manipulate our reactions to their music and insists that despite our cultural distinction between an expert class of performers and everyone else, that we are more musically equipped than we think: we are in fact hardwired for music. Music is an obsession at the heart of human nature, even more fundamental to our species than language. In "This is Your Brain on Music Levitin" offers nothing less than a new way to unlock the mysteries of the human brain.
Keywords: Music psychology; Science